DOI: 10.33915/etd.6301
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Circuits for Programming Flash Memories in Portable Applications

Abstract: Smart devices such as smart grids, smart home devices, etc. are infrastructure systems that connect the world around us more than before. These devices can communicate with each other and help us manage our environment. This concept is called the Internet of Things (IoT). Not many smart nodes exist that are both low-power and programmable. Floating-gate (FG) transistors could be used to create adaptive sensor nodes by providing programmable bias currents. FG transistors are mostly used in digital applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 104 publications
(170 reference statements)
0
8
0
Order By: Relevance
“…A 5-step design procedure can acquire a low TC while producing above-1V voltage output using the circuit of Figure 2.1. This is based off of Navidi's procedure for his circuit as detailed in [11], and by simulating the circuit with different size ratios, it was found that these steps would be appropriate for this circuit.…”
Section: Design Procedures and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 5-step design procedure can acquire a low TC while producing above-1V voltage output using the circuit of Figure 2.1. This is based off of Navidi's procedure for his circuit as detailed in [11], and by simulating the circuit with different size ratios, it was found that these steps would be appropriate for this circuit.…”
Section: Design Procedures and Resultsmentioning
confidence: 99%
“…Reference Cell with above 1V The only difference in this new circuit is the reference cell. Due to this, most of the equations applicable to Navidi's original circuit can be applied to this new circuit as well as principles of operation as described in [11].…”
Section: Chaptermentioning
confidence: 99%
See 1 more Smart Citation
“…Above 250nm, the ratio is relatively constant. 250nm and below, the ratio increases because V dd continues to scale as V tun stays relatively constant [1].…”
Section: P-type P-typementioning
confidence: 99%
“…Above 250nm, the ratio is relatively constant. 250nm and below, the ratio increases because V dd continues to scale as V tun stays relatively constant [1] Bottom plot shows the ratio of V inj to V dd . In practice, the supply V dd should be kept lower than standard V dd to prevent unwanted HEI.…”
mentioning
confidence: 99%